Effects of a Health Literacy Program on Health Behavior and Blood Sugar Levels of Older Adults in a High-Risk Group for Diabetes - Kaedpan, Kittichai; Ruangdej Chaosuansreecharoen, Kannika; Kummabu, Jeeraporn (Nursing Journal of The Ministry of Public Health, 2025)
Health literacy is a fundamental basis that enables older adults to access, understand, inquire, make decisions, and appropriately apply health information. This quasi-experimental study aimed to evaluate the effectiveness of a health literacy promotion program on health literacy, health behaviors, and fasting capillary blood glucose among older adults at risk of diabetes. The study population consisted of older adults aged 60 years and above who had fasting capillary blood glucose levels between 100 and 125 mg/dL and had never been diagnosed with diabetes. A total of 60 participants were included and divided into experimental and control groups, with 30 participants in each group, using simple random sampling combined with matching. The experimental group received a 12-week health literacy promotion program, while the control group received routine care from the sub-district health-promoting hospital. Research instruments included the Health Literacy Questionnaire (3E2S), the Health Behavior Questionnaire (3E2S), the health literacy promotion program, and the personal health record book Towards Health Literacy for Diabetes Prevention. These instruments demonstrated acceptable content validity (I-CVI = .94–1.00) and reliability (Cronbach’s alpha = .89 for the Health Literacy Questionnaire and 0.87 for the Health Behavior Questionnaire). Data were collected between February and May 2025 and analyzed using descriptive statistics, t-tests, and repeated measures ANOVA. The results showed that the experimental group had significantly higher health literacy and health behavior scores after the intervention compared with before the intervention and with the control group. Moreover, fasting capillary blood glucose decreased continuously and was significantly lower than that of the control group. In conclusion, this program was effective in promoting health and can be applied as a strategy for diabetes prevention among older adults at risk.